Analisis Rasio Keuangan dalam Mengukur Kinerja Keuangan pada PT Pos Indonesia (Persero) - Berutu, Ramadiah; Zhafira, Nabila Hilmy (Medan Resource Center, 2022)
This article aims to analyze financial ratios in measuring financial performance at PT Pos Indonesia (Persero). Analysis of the company's financial statements can be used as a reference for assessing the company's financial condition. With the analysis, it can be an indicator of a company to make the right decisions so that the company's performance will be better in the future. The instrument for assessing the good or bad condition of the company's finances is ratio analysis. Financial ratios have various types, namely liquidity, solvency, and profitability ratios. This study aims to determine the financial performance of PT. Pos Indonesia (Persero) based on financial ratio analysis. The analytical method used is quantitative method and descriptive analysis . The data and information in this research use secondary information obtained through the company's official website in the form of a financial statement document of PT Pos Indonesia (Persero) using the measurement of liquidity ratios (quick ratio, current ratio, and cash ratio) as well as one of the ratios, namely profitability (return on assets). , NPM, GPM, and ROE). Based on the liquidity ratio , namely the current ratio can not be said to be good , while the cash ratio analysis shows an increase over the last 3 years so that the condition of the company is categorized in good condition . Meanwhile, based on the profitability ratio, it describes the decline and instability so that it has not yet reached the industry standard that has been set.